Manifestasi Pendidikan Kritis di Sekolah Alam Bangka Belitung, Kota Pangkalpinang - Luna Febriani; Putra Pratama Saputra; Nopa Laura (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2018)
In industry 4.0, the education has been developing significantly. The current developing and mainstream education uses a standard-based national curriculum framework. However, nowadays it has established the new style of education as an alternative education in maintaining the balance with the existed mainstream education. Bangka Belitung Nature School is one of them which is located in Pangkalpinang City. The study aims to identify the educational learning systems in Bangka Belitung Nature School.Qualitative descriptive method was employed by analyzing the critical educational theory of Paulo Freire. The study found that the educational learning systems of Bangka Belitung Nature School were one of the alternative education which was different with the mainstream one. The educational patterns of Bangka Belitung Nature School applied the posed-problem method whereby it used the student-centered learning. Thus, the pupils in the Bangka Belitung Nature School were expected to be creative, innovative and critical in facing the social phenomena.